Mining of the Catharanthus roseus Genome Leads to Identification of a Biosynthetic Gene Cluster for Fungicidal Sesquiterpenes - Liang, J.; An, T.; Zhu, J. X.; Chen, S.; Zhu, J. H.; Peters, R. J.; Zi, J.
Characterization of cryptic biosynthetic gene clusters (BGCs)from microbial genomes has been proven to be a powerful approach to the discovery of new natural products. However, such a genome mining approach to the discovery of bioactive plant metabolites has been muted. The plant BGCs characterized to date encode pathways for antibiotics important in plant defense against microbial pathogens, providing a means to discover such phytoalexins by mining plant genomes. Here is reported the discovery and characterization of a minimal BGC from the medicinal plant Catharanthus roseus, consisting of an adjacent pair of genes encoding a terpene synthase (CrTPS18)and cytochrome P450 (CYP71D349). These two enzymes act sequentially, with CrTPS18 acting as a sesquiterpene synthase, producing 5-epi-jinkoheremol (1), which CYP71D349 further hydroxylates to debneyol (2). Infection studies with maize revealed that 1 and 2 exhibit more potent fungicidal activity than validamycin. Accordingly, this study demonstrates that characterization of such cryptic plant BGCs is a promising strategy for the discovery of potential agrochemical leads. Moreover, despite the observed absence of 1 and 2 in C. roseus, the observed transcriptional regulation is consistent with their differential fungicidal activity, suggesting that such conditional coexpression may be sufficient to drive BGC assembly in plants.